Ready to Serve Community-Based Provider Capacity to Deliver Culturally Competent, Quality Mental Health Care to Veterans and Their Families - Tanielian, Terri (RAND Corporation, 2014)
Ensuring that veterans and their families have access to high-quality mental health care is a national priority, and civilian providers are an increasingly important part of the workforce addressing veterans' mental health needs. RAND conducted a survey of civilian mental health providers to gather information about their competency with military and veteran culture and their experience treating posttraumatic stress disorder and depression.